Sr resin을 이용한 방사성 스트론튬 분리의 최적화 - 정윤희(Yoonhee Jung), 김현철(Hyun-Cheol Kim), 서경석(SUH KYUNG SUK), 강문자(Mun Ja Kang), 정근호(Kun Ho Chung) (Journal of nuclear fuel cycle and waste technology (Online), 2015)
순수 베타 핵종인 90Sr 분석은 화학적 거동이 유사한 알칼리 토금속(Ca, Ba, Ra)등 방해 원소를 제거할 분리 공정이 필요하다. 본 연구는 Sr을 추출/정제하기 위해 추출크로마토그래피법을 이용한 최적의 절차를 마련하는 것을 목적으로 한다. Sr resin 1.5 mL BV(Bed Volume)의 최대 Sr 흡착량은 6 mg이었다. 유량 1 mL min-1과 Ca 200 mg 이하에서는 Sr resin 1.5 mL(BV) 의 Sr 회수는 정량적이었으나, 유량을 5 mL min-1으로 중가 시키면 Sr 회수율이 감소하였다. 같은 양(BV)의 Sr resin을 사용 할 경우, 컬럼의 단면적이 작을수록 Sr resin의 분리능이 향상되었다. For the analysis of 90Sr, which is a pure beta emitter, radiochemical separation from the main interfering elements such as Ca, Ba and Ra is required due to their similarity in chemical behavior to strontium. This study describes a radioanalytical procedure using extraction chromatography for separating Sr from interfering elements. The maximum capacity of the resin for Sr was approximately 6 mg per 1.5 mL of bed volume (BV). The recovery of Sr on the resin 1.5 mL (BV) was quantitative for the calcium level of 200 mg at the flow rate of 1 mL min-1. However the chemical yield declined by increasing the flow rate by up to 5 mL min-1 even at the calcium level of 200 mg. When using the same BV of Sr resin, the performance of the resin was enhanced as the cross-sectional area of the Sr resin column is small.